Association of egg intake with risks of cardiometabolic factors among adults in China - Jiao, Yingying; Li, Weiyi; Jiang, Hongru; Wang, Liusen; Wang, Shaoshunzi; Hao, Lixin; Jia, Xiaofang; Wang, Zhihong; Wang, Huijun; Zhang, Bing; Ding, Gangqiang (Frontiers in Public Health, 2022)
Objective To explore the association and dose-response relationship between egg intake and cardiometabolic factors (CMFs) in Chinese adults. Methods Adults aged 18-64 who participated in at least two follow-up surveys in China Health and Nutrition Survey in 2009, 2015 and 2018 and had complete survey data and had no CMFs at baseline were selected as subjects. Egg intake was assessed with 3d-24h dietary recalls in all waves. Multivariate Cox proportional risk regression model and restricted cubic spline (RCS) model were used to analyze the association and dose-response relationship between egg intake and CMFs. Results Of the 6,182 participants who did not have metabolic syndrome (MetS) at baseline, 1,921 developed this disease during an average follow-up of 5.71 years, with an incidence of 31.07%. Central obesity, elevated TG, decreased HDL-C, elevated blood pressure and elevated plasma glucose were 38.65%, 26.74%, 30.21%, 40.64% and 30.64%, respectively. After adjusting for demographic characteristics, lifestyle, energy and BMI, using the lowest quintile (Q1) as a reference, the risk of central obesity, elevated TG, decreased HDL-C, and elevated plasma glucose in the highest quintile (Q5) were reduced by 15% (HR=0.85, 95%CI =0.73-0.98, P =0.16) , 33% (HR=0.67, 95%CI =0.57-0.78), 25% (HR = 0.75, 95% CI = 0.63 0.90, p = 0.05) and 28% (HR = 0.72, 95% CI = 0.63 0.83, p < 0.05) , respectively. The risk of elevated blood pressure was reduced by 26% in the fourth quintile (HR=0.74, 95%CI =0.64-0.85, P =0.85). RCS analysis show that the overall correlation and nonlinear relationship between egg intake and CMFs were statistically significant (P <0.05). When the intake was lower than 20g/d, the risk of MetS, central obesity, elevated blood pressure and elevated plasma glucose were negatively correlated with egg intake, while elevated TG was negatively correlated with eggs when the intake was lower than 60g/d. There was no statistically significant association between egg intake and CMFs at higher egg intake. Conclusion There was a U-shaped association between egg intake and CMFs in Chinese adults.